High-adsorbability porous matrix as well as preparation method and application thereof
By preparing highly adsorption porous substrates and using materials such as polyvinyl alcohol and crosslinking agents, the problem that existing water quality purification methods are difficult to deal with surface source pollutants is solved, and efficient water quality purification effect is achieved.
Patent Information
- Application Number
- CN202411716864.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
Smart Images

Figure CN119461635A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water purification, and in particular relates to a highly adsorbent porous matrix and a preparation method and application thereof. Background Art
[0002] The degradation of freshwater ecosystems, including rivers, lakes and other water bodies, is a major ecological problem facing the world. Among them, water pollution is one of the most important causes of the degradation of aquatic ecosystems. As a country with scarce freshwater resources, my country also faces serious water pollution problems. Chemical oxygen demand (COD), ammonia nitrogen (NH 4 + The large-scale discharge of pollutants such as total nitrogen (TN) and total phosphorus (TP) seriously threatens the health of aquatic ecosystems, and may affect water quality safety and restrict the development of the national economy.
[0003] In recent years, with my country's continuous investment in pollution control, pollutants entering water bodies are decreasing year by year, and the water quality of rivers, lakes and other water bodies is gradually improving. However, current water pollution control measures are mainly based on point source pollutant treatment and rural environmental infrastructure construction, lacking effective measures for non-point source pollution control. Agricultural source water pollutants, including non-point source pollutants generated by planting, livestock and poultry farming, aquaculture, etc., have become the main source of pollutants such as chemical oxygen demand and total phosphorus in water bodies. There is an urgent need for efficient non-point source pollutant control methods to improve water quality. In addition, the purification of endogenous pollutants in lakes and reservoirs also depends on the research and development of more efficient water purification technologies.
[0004] At present, water purification methods are mainly divided into physical, chemical and biological methods. Among them, chemical methods are prone to introduce secondary pollution and are less used. Physical methods usually remove particulate matter and suspended solids based on physical filtration. They have the advantages of simple operation and high economy. They can be combined with biological methods to further improve the water purification effect through microorganisms. Physical filtration has high requirements for the matrix. First, the matrix material should have good economy and stability to meet the needs of large-scale water purification. Secondly, the matrix material needs to have good adsorption of pollutants. At the same time, the matrix also needs to have good mass transfer and biological affinity to ensure the purification effect. This brings great challenges to the screening of filtration matrices.
[0005] CN1883787A discloses a method for preparing spherical bentonite by polyvinyl alcohol embedding. The spherical bentonite particles prepared by the method have good adsorption effects on organic matter and heavy metals. However, the particles embedded by the polyvinyl alcohol-boric acid method have strong water absorption and are prone to expansion over time, making them difficult to be used for long-term water purification.
[0006] Gao Xiang (2008) used sodium carboxymethyl cellulose and aluminum nitrate solution to prepare shaped activated carbon. Although the prepared activated carbon block has a good treatment effect on heavy metal ions, it easily swells in water and is difficult to be actually applied to large-scale water purification.
[0007] Zheng Huanan et al. (2019) used sodium alginate and polyvinyl alcohol to fix nitrified sludge to make immobilized particles, and added biochar to improve the mechanical strength. It has a good adsorption effect on ammonia nitrogen and has good mass transfer properties. However, the sodium alginate-polyvinyl alcohol embedded particles still have swelling problems, and the application range of the prepared granular preparation is relatively narrow.
[0008] CN116813372A discloses a composite porous matrix for artificial wetlands and a preparation method thereof. The porous matrix is prepared by bonding carbonized particles, construction concrete waste, high-calcium fly ash, etc., and undergoing high-temperature carbonization and crushing. However, the mass transfer and bioaffinity of the inorganic matrix material are difficult to guarantee.
[0009] Wang et al. (2024) disclosed a method for preparing a hydrophilic sponge ball carrier using polyvinyl alcohol, chitosan, and carboxymethyl cellulose. The carrier has a good microbial immobilization effect, but the adsorption and filtration effects of pollutants on the carrier are difficult to guarantee, and the application cost of the carrier is relatively high.
[0010] Therefore, there is still a need to develop new substrate preparation methods and water purification technologies for application in water pollutant treatment. Summary of the invention
[0011] To solve the above problems, the present invention provides a method for preparing a highly adsorbent porous substrate, comprising the following steps:
[0012] S1: Preparation of matrix particles;
[0013] S2: adding a binder and a cross-linking agent to the matrix particles and mixing them;
[0014] S3: Fixing and shaping the matrix particles into the highly adsorbent porous matrix.
[0015] In a specific embodiment, the binder is a polyvinyl alcohol sol with a mass concentration of 60-150 g / L.
[0016] In a specific embodiment, the cross-linking agent is obtained by mixing formaldehyde with a sulfuric acid solution, wherein the volume fraction of formaldehyde in the cross-linking agent is 5%-25%, and the volume fraction of sulfuric acid is 5%-20%.
[0017] Polyvinyl alcohol has a wide range of bonding capabilities, and can bond various materials, such as wood chips, fibers, etc. It is also highly water-resistant and environmentally friendly, and is an ideal adhesive. However, in practice, we have found that the matrix immobilized with only polyvinyl alcohol has a large water swelling property and is fragile. After being combined with the above-mentioned cross-linking agent, this aspect has been improved. The matrix of the present invention is not only stable in nature, but also highly hydrophilic and has good bioaffinity.
[0018] In a specific embodiment, the matrix particles have a particle size of 0.15-5 mm.
[0019] In a specific embodiment, the material for preparing the matrix particles in S1 can be selected from natural materials, such as soil, sediment, and straw. These natural materials are not only extremely abundant in source, but also generally have strong adsorption capacity and bioaffinity, which is conducive to the attachment of microorganisms and the rapid degradation of pollutants.
[0020] The material for preparing the matrix particles can also be selected from processed substances, such as pottery sand, activated carbon, and activated sludge. These substances are generally by-products in the production process, and the economic cost is relatively low, but due to the fine particle shape, it is difficult to directly apply them to water purification. The method of the present invention not only realizes the effective utilization of these substances, but also shows a good water purification effect.
[0021] The material for preparing the matrix particles can also be selected from other synthetic materials, such as nanomaterials. By using nanomaterials with specific properties, it is possible to achieve efficient removal of pollutants, including heavy metals, persistent organic pollutants (POPs) and other difficult-to-degrade substances.
[0022] In a specific embodiment, the ratio of the matrix particle mass (g) to the binder volume (ml) is 1:1-15:1, and the ratio of the binder volume to the crosslinking agent volume is 2:1-5:1.
[0023] In a specific embodiment, in S2, other active substances are further added, and the other active substances are selected from one or more of surfactants, stabilizers and pore formers.
[0024] By adding active substances, the bioaffinity and stability of the prepared matrix can be further increased, and the porosity can be increased, further improving the water permeability of the matrix.
[0025] The present invention also provides a highly adsorbent porous matrix prepared by the method.
[0026] The highly adsorbent porous matrix of the present invention is not only stable in nature, but also has a strong adsorption capacity for pollutants, is conducive to the attachment of microorganisms, effectively improves the removal and degradation capacity of water pollutants, and has a wide range of application potentials in water purification.
[0027] The present invention also provides application of the highly adsorbent porous matrix in water purification.
[0028] In a specific embodiment, the present invention provides a method for purifying water, comprising treating polluted water using the highly adsorbent porous matrix described above.
[0029] In a specific embodiment, the water purification method of the present invention further comprises attaching microorganisms to the highly adsorbent porous substrate before using it for treating polluted water. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The highly adsorbent porous matrix of Example 1 and its morphology in water.
[0031] Figure 2 The highly adsorbent porous matrix of Example 2 and its morphology in water.
[0032] Figure 3 It is the highly adsorbent porous matrix of Example 3.
[0033] Figure 4 The removal effect of the highly adsorbent porous matrix on water turbidity in Example 1. C is the control group, T1 is the prepared matrix group, and T2 is the unfixed particle group. Different letters above the bar graph indicate significant differences (p<0.05).
[0034] Figure 5 The effect of the highly adsorbent porous matrix on the nitrite nitrogen concentration in water of Example 1. C is the control group, T1 is the prepared matrix group, and T2 is the unfixed particle group. Different letters above the bar graph indicate significant differences (p<0.05).
[0035] Figure 6 The removal effect of the highly adsorbent porous matrix on water turbidity in Example 2. C is the control group, T1 is the group with less matrix, and T2 is the group with more matrix. Different letters above the bar graph indicate significant differences (p<0.05).
[0036] Figure 7 The removal effect of the highly adsorbent porous matrix on total nitrogen in water of Example 2. C is the control group, T1 is the group with less matrix, and T2 is the group with more matrix. Different letters above the bar graph indicate significant differences (p<0.05).
[0037] Figure 8 The removal effect of the highly adsorbent porous matrix on total phosphorus in water of Example 2. C is the control group, T1 is the group with less matrix, and T2 is the group with more matrix. Different letters above the bar graph indicate significant differences (p<0.05).
[0038] Fig. 9The effect of the highly adsorbent porous matrix on the permanganate index of water bodies in Example 3. C is the control group, T1 is the group with less matrix, and T2 is the group with more matrix. Different letters above the bar graph indicate significant differences (p<0.05).
[0039] Fig.10 The effect of the highly adsorbent porous matrix on the nitrite nitrogen concentration in water of Example 3. C is the control group, T1 is the group with less matrix, and T2 is the group with more matrix. Different letters above the bar graph indicate significant differences (p<0.05). DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings and specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0041] 1. Preparation method of highly adsorbent porous matrix
[0042] The highly adsorbent porous matrix for removing water pollutants of the present invention is prepared by the following method:
[0043] S1: Screen materials with high adsorption capacity for pollutants and dry and crush them into fine particles;
[0044] S2: Add adhesive and cross-linking agent and mix thoroughly;
[0045] S3: Fixing and shaping the matrix particles into the highly adsorbent porous matrix.
[0046] 2. Example of Preparation of Porous Matrix
[0047] Example 1 Preparation of highly adsorbent porous ceramsite matrix
[0048] The porous ceramsite matrix of this embodiment includes the following components: ceramic sand, a binder, and a cross-linking agent.
[0049] The adhesive was prepared by the following method: 80 g of polyvinyl alcohol particles were weighed, 800 ml of pure water was added, and the mixture was stirred and dissolved in a 70° C. water bath until a transparent colloidal liquid was obtained.
[0050] The cross-linking agent was prepared by the following method: 50 ml (50% v / v) formaldehyde was dissolved in 200 ml pure water, and then 30 ml concentrated sulfuric acid was added and mixed well.
[0051] The preparation method of the ceramsite matrix is as follows: add 80 ml of adhesive to 80 g of ceramsite sand with a particle size of 0.15-2 mm, mix thoroughly, add 40 ml of cross-linking agent, mix thoroughly, then put the glued particles into a mold, and place them in a 60°C water bath for 12 hours until the particles solidify to obtain a highly adsorbent porous ceramsite matrix. Figure 1The following are photos of the porous ceramsite substrate of this embodiment and photos of the porous ceramsite substrate immersed in water.
[0052] Example 2 Preparation of highly adsorbent porous rice straw matrix
[0053] The porous rice straw matrix of this embodiment includes the following components: rice straw fragments, a binder, and a cross-linking agent.
[0054] The adhesive was prepared by the following method: 80 g of polyvinyl alcohol particles were weighed, 800 ml of pure water was added, and the mixture was stirred and dissolved in a 70° C. water bath until a transparent colloidal liquid was obtained.
[0055] The cross-linking agent was prepared by the following method: 50 ml (50% v / v) formaldehyde was dissolved in 200 ml pure water, and then 30 ml concentrated sulfuric acid was added and mixed well.
[0056] The preparation method of the rice straw matrix is as follows: add 30 ml of adhesive to 8 g of rice straw fragments (about 5 mm long), mix thoroughly, add 15 ml of cross-linking agent, mix thoroughly, then put the glued particles into a mold, and place them in a 60°C water bath for 12 hours until the particles solidify to obtain a highly adsorbable porous rice straw matrix. Figure 2 The following are photos of the porous rice straw matrix of this embodiment and the photo of it floating on the water surface.
[0057] Example 3 Preparation of highly adsorbent porous sediment matrix
[0058] The porous sediment matrix of this embodiment includes the following components: sediment particles, a binder, and a cross-linking agent.
[0059] The bottom mud particles are prepared by the following method: collecting the bottom mud of the aquaculture pond, naturally air-drying it, and grinding it into particles of about 1 mm.
[0060] The adhesive was prepared by the following method: 80 g of polyvinyl alcohol particles were weighed, 800 ml of pure water was added, and the mixture was stirred and dissolved in a 70° C. water bath until a transparent colloidal liquid was obtained.
[0061] The crosslinking agent was prepared by the following method: 50 ml (50% v / v) formaldehyde was dissolved in 200 ml pure water, and then 30 ml concentrated sulfuric acid was added and mixed well.
[0062] The preparation method of the sediment matrix is as follows: the sediment particles are pre-treated with an appropriate amount of adhesive and cross-linking agent, dried and ground into powder, 80 ml of adhesive is added to 80 g of powder, mixed thoroughly, and then 40 ml of cross-linking agent is added and mixed thoroughly. Then the bonded powder is placed in a mold and placed in a 60°C water bath for 12 hours until the powder solidifies to obtain a highly adsorbable porous sediment matrix. Figure 3 This is a photo of the porous sediment matrix of this embodiment.
[0063] The prepared highly adsorbent porous sediment matrix was repeatedly washed in pure water for several times until the effluent became clear, and then soaked in pure water for more than 24 hours. Then, the sediment matrix was transferred to the tail water collected from the breeding pond, and the Bacillus subtilis preparation (effective viable bacteria count ≥ 40 billion / g) was added and aerated for more than 72 hours.
[0064] 3. Water pollutant purification test
[0065] (1) Test 1
[0066] The highly adsorbent porous ceramsite matrix of Example 1 was used for the test, and the ceramic sand particles not treated by the method of the present invention were used as a control. Before the test, the matrix and the ceramic sand particles were washed with pure water and test water for multiple times until the water was clear. The test water was collected from the breeding pond of the Yaowan Test Base of the Yangtze River Fisheries Research Institute, and its main water quality indicators are shown in Table 1.
[0067] Table 1 Main water quality indicators of water used in test 1
[0068]
[0069] The prepared highly adsorbent porous ceramsite matrix and the ceramic sand particles not treated by the method of the present invention were used to treat the test water body. The test was carried out in a 500ml polyethylene bottle, and the porous ceramsite matrix and the ceramic sand particles were added to the bottle respectively, and the ratio of the porous ceramsite matrix and the ceramic sand particles to water was about 1:5. In addition, a test group was set up without adding any substance as a control group. Each test group was set up in 3 parallels and aerated for 12 hours at room temperature. Then water samples were collected respectively to measure the differences in different water quality indicators.
[0070] The results show that the highly adsorbent porous ceramsite matrix of Example 1 has a good removal effect on turbidity, with a removal rate of 70.85% ( Figure 4 In addition, the highly adsorbent porous ceramsite matrix of Example 1 also has a good adsorption effect on ammonia nitrogen and organic matter, and may have a good ammonia oxidation function, and the nitrite nitrogen concentration in the water body increased by 29.92% ( Figure 5 ). In particular, compared with ceramic sand particles, the highly adsorbent porous ceramsite matrix of the present invention does not have the problem of increasing suspended solids in water, exhibits better adsorption effect, and may also exhibit better microbial oxidation activity.
[0071] (2) Test 2
[0072] The highly adsorbent porous rice straw matrix of Example 2 was used for the test. Before the test, the matrix was washed several times with pure water and test water respectively until the water was clear. The test water was collected from the aquaculture pond of the Yaowan Test Base of the Yangtze River Fisheries Research Institute. Its main water quality indicators are shown in Table 2.
[0073] Table 2 Main water quality indicators of water used in test 2
[0074]
[0075] The prepared highly adsorbent porous rice straw matrix was used to treat the test water. The test was carried out in a 500ml polyethylene bottle, and different amounts of highly adsorbent porous rice straw matrix were added to the bottle, and the ratio of matrix to water was about 1:10 (less matrix group) and 1:5 (more matrix group). In addition, a test group was set up without adding any substance as a control group. Each test group was set up with 3 parallels and aerated for 12 hours at room temperature. Then water samples were collected and the differences in different water quality indicators were measured.
[0076] The results showed that the highly adsorbent porous rice straw matrix of Example 2 had a good removal effect on turbidity, total phosphorus and total nitrogen, and the removal rate increased with the increase of the matrix dosage ( Figure 6-8 ), and the activity of heterotrophic microorganisms may also be enhanced to a certain extent. Compared with the control, the removal rates of total nitrogen and total phosphorus in the more substrate group reached 45.52% and 58.97%, respectively, and the turbidity of the water body decreased by 69.55%.
[0077] (3) Test 3
[0078] The highly adsorbent porous sediment matrix of Example 3 was used for testing to analyze its effect on the fixation of microorganisms and water purification. The test water was collected from the breeding pond of the Yaowan Experimental Base of the Yangtze River Fisheries Research Institute, and its main water quality indicators are shown in Table 3. The matrix was washed with pure water and test water for multiple times until the effluent was clear. The sediment matrix was then transferred to the tail water collected from the breeding pond, and a Bacillus subtilis preparation (effective viable count ≥ 40 billion / g) was added and aerated for more than 72 hours.
[0079] Table 3 Main water quality indicators of water used in test 3
[0080]
[0081] Before the test, the highly adsorbent porous sediment matrix with fixed microorganisms was washed several times with pure water and test water until the effluent was clear to remove the microorganisms on the surface of the matrix. The test was carried out in a 500ml polyethylene bottle, and different amounts of highly adsorbent porous sediment matrix with fixed microorganisms were added to the bottle, and the ratio of matrix to water was about 1:10 (less matrix group) and 1:5 (more matrix group). In addition, a group of test groups was set up without adding any substances as a control group. Each test group was set up with 3 parallels and aerated for 12 hours at room temperature. Then water samples were collected separately to measure the differences in different water quality indicators.
[0082] The results showed that the highly adsorbent porous sediment matrix of Example 3 had a good fixation effect on microorganisms. After adding the matrix, the CODMn There was a significant increase ( Fig. 9 ), indicating that microorganisms in the water sample multiplied in large numbers and were highly active, causing NO 2 - The concentration increased significantly ( Fig.10 ). In addition, the increase in different indicators increased with the increase in the amount of substrate, indicating that increasing the amount of substrate can help further improve the activity of microorganisms. 2 - The concentration increased by 37.51%. As the main group involved in the transformation of pollutants, the increase in the number and activity of microorganisms can ensure the efficient purification of water pollutants.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly adsorbent porous matrix, characterized in that: The following steps are involved: S1: Preparation of matrix particles; S2: adding a binder and a cross-linking agent to the matrix particles and mixing them; S3: Fixing and shaping the matrix particles into the highly adsorbent porous matrix.
2. The method according to claim 1, characterized in that The adhesive is a polyvinyl alcohol sol with a mass concentration of 60-150 g / L, and the cross-linking agent is a mixed solution of formaldehyde and sulfuric acid, wherein the volume fraction of formaldehyde is 5%-25% and the volume fraction of sulfuric acid is 5%-20%.
3. The method according to claim 1, characterized in that The particle size of the matrix particles is 0.15-5 mm.
4. The method according to claim 1, characterized in that: The material for preparing the matrix particles in S1 is selected from one or more of soil, sediment, straw, pottery sand, activated carbon, activated sludge, and nanomaterials.
5. The method according to claim 1, characterized in that The ratio of the mass (g) of the matrix particles to the volume (ml) of the binder is 1:1-15:1; the ratio of the volume of the binder to the volume of the cross-linking agent is 2:1-5:
1.
6. The method according to any one of claims 1 to 5, characterized in that In S2, other active substances are also added, and the other active substances are selected from one or more of surfactants, stabilizers and pore formers.
7. A highly adsorbent porous matrix, characterized in that: It is prepared by the method according to any one of claims 1 to 6.
8. A water purification method, characterized in that: The method comprises using the highly adsorbent porous matrix described in claim 7 to treat polluted water.
9. The method according to claim 8, characterized in that The method also includes subjecting the highly absorbent porous matrix to microbial attachment before using the matrix to treat polluted water.
Citation Information
Patent Citations
Constructed wetland composite porous substrate and preparation method thereof
CN116813372A
Semi-coke microbial carrier and preparation method thereof
CN103253776A
Filler with salt-tolerant functional microorganism enrichment effect and preparation method thereof
CN112390347A
Biological fluidization carrier material as well as preparation method and application thereof
CN115197515A
Biological carrier material for sewage treatment and preparation method thereof
CN115418066A